Evaluation of excavation-induced movements through case histories in Hangzhou. Issue 6 (7th February 2020) - Ying, Hong-Wei; Cheng, Kang; Zhang, Li-Sha; Ou, Chang-Yu; Yang, Yong-Wen
Abstract : Purpose: Deep excavation in soft clay often causes additional deformations to surroundings. Then, if deformations cannot be predicted reasonably, the adjacent buildings may be threatened by the deep excavation. Based on the good field observations from ten deep excavations in Hangzhou, this paper aims to thoroughly investigate the characteristics of wall deflections and ground settlements induced by deep excavations. Design/methodology/approach: On the basis of good field observation of ten deep excavations, the performances of excavations, supported by contiguous pile in Hangzhou, were studied, and also compared with other case histories. Findings: The maximum wall deflections (dhm) rang mostly from 0.7 to 1.2 per cent He, where He is the final excavation depth, larger than those in Taipei and Shanghai. The observed maximum ground settlement in the Hangzhou cases generally ranges from 0.2 to 0.8 per cent He . Then, the settlement influence zone extends to a distance of 2.0-4.0 He from the excavation. The relatively large movements and influence zones in Hangzhou may be attributed to low stability numbers, large excavation widths and the creep effect. The excavation width is justified to have a significant influence on the wall deflection. Therefore, to establish a semi-empirical formula for predicting the maximum wall deflection, it is necessary to include the factor of excavation width. Originality/value: The relevant literature concentrated on the characteristics of deep excavations supported by the contiguous pile wall in Hangzhou soft clay can rarely be found. Based on the ten deep excavations with good field observation in Hangzhou, the characteristics of wall deflection and ground settlements were comprehensively studied for the first time, which can provide some theoretical support for similar projects.